Can constitutive rules create a practice? - Giuseppe Lorini (Revista Opinião Jurídica, 2015)
The author investigates the role of constitutive rules in the construction of social reality. He denies that constitutive rules are a sufficient condition of a practice such as a chess game. To create a new practice with rules, it is necessary that there already be the grammar of this practice, that is, the sense of this practice (for example, the sense of game). It is the grammar of a practice and not its constitutive rules that determines the nature of a practice. The sense of a practice cannot be created by constitutive rules.